2017
DOI: 10.1093/bja/aex239
|View full text |Cite
|
Sign up to set email alerts
|

Age and other perioperative risk factors for postoperative systemic inflammatory response syndrome after cardiac surgery

Abstract: We have demonstrated that advanced patient age is associated with a decreased risk of postoperative SIRS among cardiac surgery patients, where patients aged over 72 yr had the lowest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…Interestingly, a recent study showed that age >72 years was associated with decreased incidence of postoperative systemic inflammatory response syndrome in the first 24 hours after cardiac surgery. 38 The clinical significance of our findings of higher risk for sepsis development in the elderly population warrants further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, a recent study showed that age >72 years was associated with decreased incidence of postoperative systemic inflammatory response syndrome in the first 24 hours after cardiac surgery. 38 The clinical significance of our findings of higher risk for sepsis development in the elderly population warrants further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…The inflammatory response after cardiac surgery has been widely recognized [4, 14, 15]; however, few studies have focused on its occurrence following repair of aortic pathology, especially its severity. SIRS, defined when the patient met two or more criteria, is seen in 96.2% of patients after cardiac surgery, without any discriminatory value for predicting clinical outcomes [6].…”
Section: Discussionmentioning
confidence: 99%
“…This kind of nonintensive inflammation reaction uniquely linked to advancing age has strong evidence in clinical work. There was striking evidence that the risk of SIRS at any time within 24 h after cardiac surgery is uniquely attenuated in patients aged 72 yr or older [4]. It is hypothesized that the phenotypic and genomic variation and patients’ susceptibility had good perioperative predictability of the individual inclination to develop inflammatory syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Іншим важливим механізмом, що впливає на морфофункціональний стан формених елементів крові, є контакт крові із синтетичною поверхнею екстракорпорального контура, який стає тригером розвитку системної запальної відповіді (СЗВ) [15]. Розвиток синдрому системної запальної відповіді обумовлений досить великою площею контакту з неендотелізованою поверхнею екстракорпорального контура й відсутністю повної біосумісності його матеріалів із кров'ю [16,17].…”
Section: вступunclassified